2022
DOI: 10.18502/jthc.v16i3.8188
|View full text |Cite
|
Sign up to set email alerts
|

Very Early Discharge of Patients with ST-Segment-Elevation Myocardial Infarction after Primary Percutaneous Coronary Intervention

Abstract: Background: The discharge of uncomplicated patients with ST-segment-elevation myocardial infarction (STEMI) within 48 to 72 hours has been proven safe and feasible. The safety and feasibility of the very early discharge (≤48 h) of such patients, especially during the COVID-19 pandemic with limited bed availability and infection risk, have yet to be evaluated. Methods:  In this cohort study on 108 patients with STEMI who presented to Farshchian Heart Center between February and May 2020, 30 patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
2
0
2
Order By: Relevance
“… 8 Apart from that, patients in the low-risk category are also indicated as not experiencing any complications. 7 , 15 , 29 , 32 Most complications in post-PPCI STEMI patients, such as arrhythmias, cardiogenic shock, and bleeding or recurrent ischemic events, occur within the first 24–72 hours. 33 Previous studies also reported that as many as 5745 STEMI patients treated with PPCI showed that 90% of ventricular tachycardia or ventricular fibrillation occurred within 48 hours after symptoms appeared.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Apart from that, patients in the low-risk category are also indicated as not experiencing any complications. 7 , 15 , 29 , 32 Most complications in post-PPCI STEMI patients, such as arrhythmias, cardiogenic shock, and bleeding or recurrent ischemic events, occur within the first 24–72 hours. 33 Previous studies also reported that as many as 5745 STEMI patients treated with PPCI showed that 90% of ventricular tachycardia or ventricular fibrillation occurred within 48 hours after symptoms appeared.…”
Section: Discussionmentioning
confidence: 99%
“…Una revisión sistemática y metaanálisis 8 publicada en 2020, que incluyó siete ensayos clínicos aleatorizados (ECA) con un total de 1780 pacientes y cuatro estudios observacionales con 39,288 pacientes, no demostró diferencias significativas en términos de mortalidad por todas las causas (riesgo relativo [RR]: 0.97; intervalo de confianza del 95% [IC95%]: 0.23-4.05) y eventos cardiovasculares mayores (MACE, major adverse cardiovascular events) (RR: 0.84; IC95%: 0.56-1.26) entre el egreso precoz y el convencional en sujetos de bajo riesgo. Sin embargo, los estudios observacionales demostraron una reducción significativa de la mortalidad total (RR: 0.40; IC95%: 0.23-0.71) y de los MACE (RR: 0.41; IC95%: 0.26-0.78), y sin diferencias en rehospitalizaciones, entre el alta temprana y la tardía 9 .…”
Section: Pregunta 1 ¿Es Seguro Dar El Alta Temprana (A Las 48-72 Hora...unclassified
“…La dislipidemia se debe controlar con tratamiento farmacológico e intervenciones en el estilo de vida en los pacientes que han sufrido un SCA, debido a que se trata de uno de los principales factores de riesgo del inicio y la progresión de la enfermedad coronaria. De hecho, el colesterol debe considerarse como un factor etiopatogénico y no solo como un factor de riesgo [1][2][3][4][5][6][7][8][9][10][11] . Las estatinas son los fármacos hipolipidemiantes de elección [279][280][281][282][283][284][285][286][287][288][289][290] .…”
Section: Pregunta 1 ¿Cuáles Son Las Metas De Colesterol Y Qué Fármaco...unclassified
“…Cardiovascular diseases (CVDs) are one of the leading causes of mortality and morbidity, responsible for 1 in every 2 to 3 deaths (1 death every 40 seconds) in the United States. 1 , 2 Heart failure (HF), the common endpoint of CVDs, 3 is estimated to affect more than 8 million people (prevalence =1 in every 33 individuals) in the United States by 2030. 4 The increasing prevalence and mortality rates of HF have prompted enormous studies to identify its specific symptoms, risk factors, and survival rate.…”
Section: Introductionmentioning
confidence: 99%